2016
DOI: 10.1017/jpa.2016.84
|View full text |Cite
|
Sign up to set email alerts
|

Paleobiology of firmground burrowers and cryptobionts at a Miocene omission surface, Alcoi, SE Spain

Abstract: A well-preserved omission surface (sedimentary discontinuity) in an outcrop near Alcoi in southeastern Spain displays trace fossils and body fossils that reflect a dynamic benthic community during the Miocene (Langhian–Tortonian). This outcrop, besides being the type locality of Spongeliomorpha iberica Saporta, 1887, exhibits other abundant trace fossils, such as Glossifungites saxicava Łomnicki, 1886 and Gastrochaenolites ornatus Kelly and Bromley, 1984. These trace fossils are restricted to a single stratigr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 64 publications
(82 reference statements)
1
10
0
Order By: Relevance
“…As noted by Uchman et al (2000), in the G. saxicava type area, the width of smaller specimens of G. saxicava is rather consistent across the axial length, whereas in larger forms, the trace widens distally. A similar disparity is present in G. saxicava specimens of Belaústegui et al (2016a). This covariation of size and shape is also observed in specimens of G. gingrasi n. isp.…”
Section: Glossifungites Gingrasi New Ichnospeciessupporting
confidence: 77%
See 3 more Smart Citations
“…As noted by Uchman et al (2000), in the G. saxicava type area, the width of smaller specimens of G. saxicava is rather consistent across the axial length, whereas in larger forms, the trace widens distally. A similar disparity is present in G. saxicava specimens of Belaústegui et al (2016a). This covariation of size and shape is also observed in specimens of G. gingrasi n. isp.…”
Section: Glossifungites Gingrasi New Ichnospeciessupporting
confidence: 77%
“…More recently, Knaust (2013) concluded that there are only two valid ichnospecies of Rhizocorallium (R. jenense and R. commune Schmid, 1876), and following Fürsich (1974), included Glossifungites under Rhizocorallium, although the two papers are not in complete agreement on the classification with regards to the importance of spreite versus passive fill or ichnotaxobase hierarchy (ichnospecies versus ichnosubspecies and variety). More recently, Belaústegui et al (2016a) refuted that Glossifungites was a junior synonym of Rhizocorallium, King et al-Glossifungites gingrasi n. isp., a probable subaqueous insect domicile and reintroduced Glossifungites saxicava as a valid ichnospecies using examples from Spain that contained barnacle-colonized interiors to illustrate the importance of differentiating passive versus active fills and the presence/absence of spreite as ichnotaxobases for differentiating ichnogenera.…”
Section: Systematic Ichnologymentioning
confidence: 99%
See 2 more Smart Citations
“…Several ichnotaxa were registered in the Glossifungites Ichnofacies and characterize different feeding behaviours. The majority of this record include Conichnus , Skolithos , Diplocraterion , Arenicolites , Gastrochaenolites , and Bergaueria (suspension feeders), Thalassinoides, Glossifungites , and Psilonichnus (deposit‐feeders), Spongeliomorpha (deposit‐feeders or farming behaviour), and Palaeophycus (suspension feeders, deposit‐feeders or carnivores) (e.g., Abdel‐Fattah, Gingras, Caldwell, Pemberton, & MacEachern, 2016; Balistieri & Netto, 2002; Belaústegui, Ekdale, Domènech, & Martinell, 2016; Bromley & Allouc, 1992; Buatois & Encinas, 2006; Buatois, Mángano, Alissa, & Carr, 2002; Carmona, Ponce, Mángano, & Buatois, 2006; Dasgupta & Buatois, 2012; Fielding, Bann, MacEachern, Tye, & Jones, 2006; Gandini, Netto, Kern, & Lavina, 2010; Netto et al, 2007; Pearson, Mángano, Buatois, Casadío, & Raising, 2012; Pemberton & Frey, 1985; Savrda, 1991; Schultz, Furlong, & Zonneveld, 2016; Sedorko, Netto, & Savrda, 2018; Seilacher, 1967). However, burrows such as Planolites , Taenidium , Rhizocorallium , Zoophycos (deposit‐feeders), and Chondrites (chemichnion) were also attributed to trace fossil suites of the Glossifungites Ichnofacies (Cónsole‐Gonella, Griffin, & Aceñolaza, 2009; MacEachern & Burton, 2000; Uchman, Bubniak, & Bubniak, 2000), a matter that still needs review.…”
Section: Introductionmentioning
confidence: 99%